Granite outcrops as possible havens for biodiversity in arid land - Mohammed Shakdofa; Omar Almaghrabi; Emad Alsherif (Biodiversity Data Journal)
Little is known about granite outcrops in arid regions. The current study sought to determine if granite outcrops generate wetter islands compared to their arid surroundings. Forty independent phytosociological stands dealing with granite outcrops (25 stands) and nearby matrix (15 stands) vegetation were sampled. A total of 146 species of vascular plants were identified, categorised into 39 families and 106 genera. Results recorded more taxa in granite outcrops than in their matrix; specifically, there were 29.2% more species, 33.8% more genera and 26.6% more families in the granite outcrops than in their matrix. Only 16 species were reported in the matrix area that are not present in the granite outcrops, compared to 46 species found in the granite outcrops that are absent from the matrix area. The ratios of therophytes and phanerophytes in granite outcrops were 5% and 11.1% greater, respectively, than those observed in their matrices. The proportions of Sudano-Zambasian elements were higher in granite outcrops than those in the matrix and, in contrast, the Sudano-Arabian and tropical elements proportions were higher in the matrix than those in the granite outcrops. The current results concluded that granite outcrops form wetter island-like habitats as compared to their surroundings.